Exploration of Gender Role in Bisheswar Prasad Koirala’s Tinghumti - Bista, Asmita (JODEM: Journal of Language and Literature, 2019)
Bisheshwar Prasad Koirala’s novel Tinghumti is always tempting for the reader as it still reflects the relevant picture of Nepali society. In this novel the characters defy as well as define the gender roles. Influenced with revolutionary thought they defy the prescribed gender roles; but chained in age old thought they, time and again, define the traditional gender role. This article aims to identify the reasons that drive these characters to defy and define the traditional gender roles. For that Judith Butler’s and Connell’s idea of gender theory has been used. The significance of this study is to contribute a different perspective for the reader to see the novel Tinghumti showing that traditional gender roles are meddled and confirmed in it. The study concludes that in the novel, the characters defy as well as define the socially prescribed gender role because gender is socio-political construction that achieves legitimacy and naturality via perpetual observation and repetition.